Estudo numérico do conector Crestbond e de chapa passante em pilares mistos tubulares circulares preenchidos com concreto em situação de incêndio - Luiz Fernando Pereira do Prado (2017)
This research presents the study of the behavior of the Crestbond and Shear Flat used as shear load transfer in Concrete Filled Tubular Circular Columns in fire conditions. The standard ABNT NBR 14323: 2013 proposes that connections between composite beams and composite columns with concrete filled hollow sections in fire conditions are made by Bearing Blocks and Shear Flats. The Crestbond is not yet standardized, and it is extremely important to study its behavior as shear load transfer in columns. Studies about Crestbond at room temperature have already been done, however, have not yet been investigated at elevated temperature. Investigations about shear connectors in composite columns in fire conditions are scarce and did not find any experimental results in the literature. At elevated temperatures occurs the degradation of the properties of the materials and because of it, is necessary to know how the shear connectors will behave thermally and structurally in this situation. Therefore, the present work is dedicated to do a numerical investigation, through the Abaqus software, trying to understand the behavior of Crestbond and Shear Flat in composite columns at elevated temperatures. Through the state or art, this work tried to find in the literature studies about shear connectors, composite columns filled with concrete in fire conditions and numerical analyzes using the Abaqus software, to identify which aspects should be investigated in this dissertation. Then, it was made a numerical calibration of experimental results of heat transfer and structural analysis about composite columns, at elevated temperature, to be able to insert the shear connectors in the models. The behavior of Crestbond and Shear Flats was studied with different load levels and different tubes diameters to evaluated to compare how each will behave in each situation. In the thermal analyzes, independent of the diameter of the steel tube, Crestbond presented a higher temperature than the Shear Flat, but the differences were small, being at most 98 ° C and up to 12% and they occurred in only a few moments. This shows that the two connectors had very similar thermal behavior, regardless of the length of the Shear Flat. The numerical model developed presented difficulties in obtaining the results in the structural analyzes carried out with thermal expansion. For this reason, also were made simulations without the use of thermal expansion. In the results with thermal expansion, it has not remained a standard of which shear connector resists a longer time in all the diameters and levels of applied load. The behavior of the shear connectors in the analyzes without thermal expansion showed to be very different, with Shear Flat having more resistant time than Crestbond in all cases, but the majority of the results were small (less than 20%). This shows that Shear Flat had a slightly better behavior than the Crestbond, but, it´s not conclusive that can be considered better. In addition, Crestbond has the advantage of being able to provide greater ease of placement of stirrups in longitudinal bars on Composite Columns than Shear Flat